KAJIAN ATAS FAKTOR-FAKTOR YANG MEMPENGARUHI PENGUNGKAPAN LINGKUNGAN (ENVIRONMENTAL DISCLOSURE) PADA PERUSAHAAN PUBLIK DI BEJ PADA TAHUN 2004 - 2005 - Bambang Sudaryono (Media Riset Akuntansi, Auditing & Informasi, 2007)
The aim of this research is to analyze the factors that impact the public companies' enviromental disclosure and also to analyze the impact of corporate (company's size, age, ROA and earnings management) on coprporate disclosure (mandatory and voluntary). Data are obtained from 60 companies, which are listed on Jakarta Stock Exchange, and selected based on the purposive sampling method. The data analysis method is used the path analysis. The result of this research show that on the significant rate of 5%, the company's size, ROA, earnings management and corporate disclosure have a significant effect to environmental disclosure. While for the company's age and financial leverage have no significant effect to the environmental disclosure.Keywords: Enviromental disclosure, company's size, company's age, ROA and coprporate disclosure.